Mount Irvine Bay, Tobago, W.I. - (:unkn) unknown (Y. De Lima and Co. Ltd., Trinidad, 2011)
The postcard shows the Mt. Irvine Beach in Tobago. Postcard number DT-77831-B.
Colour: Coloured; Style: Landscape; Other: Unbordered, Divided
Keywords: Trinidad and Tobago; Postcards; Beaches--Trinidad and Tobago; Bays--Trinidad and Tobago; Cities and towns--Trinidad and Tobago--Mount Irving; Coconut palm--Trinidad and Tobago; Bathing beaches--Trinidad and Tobago; Seashore--Trinidad and Tobago